2008
DOI: 10.1364/oe.16.010200
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical demonstration of an optical vortex coronagraph

Abstract: Using an optical vortex coronagraph and simple adaptive optics techniques, we have made the first convincing demonstration of an optical vortex coronagraph that is coupled to a star gazing telescope. We suppressed by 97% the primary star of a resolvable binary system, Cor Caroli. The stars had an angular separation of 1.9lambda/D at our imaging camera. The secondary star suffered no suppression from the vortex lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(82 citation statements)
references
References 21 publications
0
82
0
Order By: Relevance
“…A first investigation in this field has been done by Jenkins (2008) in a paper concerning the coronagraphy, in which it was analytically demonstrated that an OV coronagraph can give good performances also in ground-based telescopes operating with a partial correction of the atmospheric turbulence. The feasibility of ground-based = 2 OV coronagraphy has been demonstrated very recently by Swartzlander et al (2008). In this Paper we present the results of the direct observation of OVs generated with starlight beams at the Asiago 122 cm telescope.…”
Section: Introductionmentioning
confidence: 94%
“…A first investigation in this field has been done by Jenkins (2008) in a paper concerning the coronagraphy, in which it was analytically demonstrated that an OV coronagraph can give good performances also in ground-based telescopes operating with a partial correction of the atmospheric turbulence. The feasibility of ground-based = 2 OV coronagraphy has been demonstrated very recently by Swartzlander et al (2008). In this Paper we present the results of the direct observation of OVs generated with starlight beams at the Asiago 122 cm telescope.…”
Section: Introductionmentioning
confidence: 94%
“…The VC suppresses the light from a star, allowing direct detection of dim companions, exoplanets, and circumstellar disks. Imaging objects with a VC, which are otherwise buried in the noise associated with the bright host star, has been demonstrated in laboratory (e.g., Mawet et al 2009;Delacroix et al 2013) and on-sky observations (e.g., Swartzlander et al 2008;Mawet et al 2010;Serabyn et al 2010;Absil et al 2013;Defrère et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…-Singular optics is the study of light waves with a phase singularity [1]. For two decades, since the experimental discovery of optical vortices [2], study of singular properties in the scalar theory of light has led to fascinating applications in various areas of physics [3][4][5][6][7][8]. Much more recently, the concepts and experimental setups from singular optics found their way to electron microscopes [9][10][11].…”
mentioning
confidence: 99%